Empowerment of Aisyiyah Cadre in making medicine boxes and using medication reminder applications to create a drug-aware society - Primanitha Ria Utami; Devi Ristian Octavia; Emilia Rahmawati; Rossy Fadia Putri (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
With the development of the times and the influence of technology in the industrial era 4.0, people tend to choose everything that can be accessed easily and instantly. Likewise with the use of drugs with a large number of therapies in one consumption, attention regarding drugs is still low. This can affect the level of compliance in taking the drug. Especially in chronic diseases that require lifestyle modification and long-term therapy. Therefore, the large number of therapies that will be consumed, especially in the elderly, it will be more practical to use a medicine box or drug alarm application as a reminder when it's time to take medicine, how much to take, what drugs to take with different indications. different. The hope is that the greater the awareness of the drugs consumed, the greater the success of therapy. This is also supported by the management of drugs in each household with the dagusibu concept. In managing medicine at home, there are still many people who do not understand how to store and dispose of medicine. People store syrup medicine in the refrigerator in the hope that the medicine will last longer even though this storage is not appropriate. So that the purpose of this community service will be able to increase public awareness in creativity independently able to assemble/make medicine boxes, increase knowledge related to caring for managing household drugs by knowing the kinds of drugs on the market, various forms of drug preparation, how to use them. medicines, how to store and dispose of medicines that are not used. The method of this service activity is a participatory community empowerment method with the Particatory Rural Appraisal (PRA) model, which is a method that emphasizes community involvement in the entire series of activities carried out, starting from making medicine boxes manually, how to use drug alarm application, and implementation in managing home medicines. stairs with the Dagusibu concept. Keywords: Application,Care for Drugs, Dagusibu, Medicine Box